2019
DOI: 10.1002/ijgo.12797
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transvaginal repair versus laparoscopic repair of lower‐segment cesarean scar defects

Abstract: Objective To evaluate transvaginal repair versus laparoscopic repair of cesarean scar defects (CSDs). Methods A retrospective cohort study was conducted among 67 symptomatic women with CSDs who attended a tertiary hospital in Beijing, China, between July 1, 2013, and March 31, 2017. The participants underwent either transvaginal repair (n=31) or laparoscopic repair (n=36). Medical costs, perioperative outcomes, and surgical outcomes were compared. Results No statistically significant between‐group differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…None of the studies included a combination of women with and without infertility. An overview of the baseline characteristics, including niche features, is reported for the studies that included women diagnosed with infertility (Table 1) (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and women without infertility (Table 2) (36)(37)(38)(39)(40). Most studies evaluated HNR (N ¼ 14), and 7, 7, and 2 studies reported on VNR, LSNR, and LTNR, respectively.…”
Section: Study and Population Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the studies included a combination of women with and without infertility. An overview of the baseline characteristics, including niche features, is reported for the studies that included women diagnosed with infertility (Table 1) (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and women without infertility (Table 2) (36)(37)(38)(39)(40). Most studies evaluated HNR (N ¼ 14), and 7, 7, and 2 studies reported on VNR, LSNR, and LTNR, respectively.…”
Section: Study and Population Characteristicsmentioning
confidence: 99%
“…For VNR, all studies used an RMT of <3 mm as the cutoff value. For LSNR, the most frequently reported cutoff value of the RMT was <3 mm (30,36,40). An exception was the study of Tanimura et al (33) who performed HNR in patients with an RMT of R2.5 mm in combination with an anteflexed or straight uterus and LSNR in women with an RMT of <2.5 mm or a uterus in retroflexion.…”
Section: Study and Population Characteristicsmentioning
confidence: 99%
“…Reported outcomes, either by patients or clinicians, are summarised in Table 3. The most frequently reported gynaecological outcomes were prolonged menstrual bleeding [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], postmenstrual spotting [5,8,9,25,35,[44][45][46][47][48][49][50], dysmenorrhoea [5,8,9,25,27], dyspareunia [5,27,46] and (chronic) pelvic pain or abdominal pain [5,24,25,27,34,40,46,51,52...…”
Section: Systematic Review Of Literaturementioning
confidence: 99%
“…Prevalence of abnormal adhesive placenta [26,27], successful vaginal birth after CS [27,[53][54][55] and uterine rupture or dehiscence [27,[56][57][58][59][60][61][62][63] were reported as obstetric outcomes. Fertility-related niche therapy studies reported on wish to conceive (secondary subfertility) [26,27,33,52], pregnancy [25,26,33,39,40,42,64] and miscarriage rate [26,27,33,39,42,43], the risk of caesarean scar pregnancy [27,33,40] and live birth rate [26,27,40,43]. Subsequent pregnancies were followed after niche therapy in four studies: mode and timing of delivery [39,42], risk of abnormal adhesive placenta [40] and risk of uterine dehiscence or rupture [39,40,43] were reported.…”
Section: Systematic Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation